Composite material porous bone repair scaffold as well as preparation method and application thereof

By adding poly(citric acid-1,8-octanediol/ethylene glycol) ester particles to the bone repair stent, the problem of mismatch between the degradation rate of the existing bone repair stent and the bone regeneration rate is solved, the mechanical properties and biological activity of the stent are improved, and the good growth and integration of bone is promoted.

CN119656374APending Publication Date: 2025-03-21TONGGUANG (SUZHOU) BIOTECHNOLOGY CO LTD +1

Patent Information

Application Number
CN202411830195.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The degradation rate of existing bone repair stents cannot match the bone regeneration rate, and the mechanical properties and biological activities are limited, which affects the bone regeneration effect.

Method used

By adding biodegradable poly(citric acid-1,8-octanediol/ethylene glycol) ester particles to bone repair organic and inorganic materials, the degradation rate of the scaffold is regulated and its mechanical properties and biological activity are improved.

Benefits of technology

The matching of the composite degradation rate and the new bone regeneration rate is achieved, the mechanical properties and biological activities of the bone repair scaffold are improved, and the good growth and integration of bone is promoted.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119656374A_ABST
    Figure CN119656374A_ABST
Patent Text Reader

Abstract

The invention provides a composite material porous bone repair scaffold as well as a preparation method and application thereof. The composite material porous bone repair scaffold is prepared from the following raw materials: a bone repair organic material, a bone repair inorganic material and poly (citric acid-1, 8-octylene glycol / ethylene glycol) ester particles. The biodegradable poly (citric acid-1, 8-octylene glycol / ethylene glycol) ester particles are added into the bone repair organic material and the bone repair inorganic material, so that the degradation rate of the bone repair scaffold can be regulated and controlled, and the degradation rate of the composite material is matched with the new bone regeneration rate; moreover, the bone repair scaffold has good biocompatibility and high osteogenic activity, the mechanical property of the bone repair scaffold can be improved, the mechanical behavior of natural bones can be simulated, and the stability of the scaffold can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of bone repair composite scaffolds and relates to a composite material porous bone repair scaffold and a preparation method and application thereof. Background Art

[0002] Bone defects are a common clinical disease that can be caused by a variety of factors, including congenital anomalies, high-energy trauma, open fractures, bone loss, bone tumor resection, and bone infection requiring debridement. Bone defect repair is the most common regenerative surgery, and approximately 2 million bone grafts are required worldwide each year. Bone tissue is a natural nanocomposite material with a layered structure composed of organic proteins (mainly collagen), inorganic minerals (mainly calcium phosphate), and a variety of cells (osteoblasts, osteoclasts, stem cells, etc.). Multiple factors can promote bone tissue repair, including good mechanical support, nutrient delivery, cell adhesion and proliferation, osteoconduction (biomineralization deposition), and osteogenesis. Therefore, bone tissue engineering materials are generally designed based on the physical structure and functional design of bone tissue to promote the growth of new bone tissue and restore its function. An ideal bone tissue engineering scaffold should have multiple functions, including biomimetic structural properties, controllable biodegradation, excellent biocompatibility and antibacterial activity, good bone conductivity, and osteoinductivity. The biomineralization ability and osteogenic bioactivity of the scaffolds can also provide a suitable environment for bone integration, osteoblast growth, and osteoblast differentiation, thus promoting good bone growth.

[0003] Organic / inorganic composite materials have significant advantages in bone repair scaffolds. They combine the biocompatibility of organic polymers and the osteoinductivity of inorganic materials, and can effectively promote bone regeneration. The mechanical properties of the material are enhanced, providing sufficient support, and the degradation rate can be precisely controlled by adjusting the proportion of components to match the needs of bone healing. In addition, the composite material has an adjustable pore structure, which is suitable for cell attachment and tissue growth, and the anti-infection ability can be improved by introducing antibacterial components. This type of material is widely used in the repair of complex bone defects and has great clinical potential. For example, poly-ε-caprolactone / β-tricalcium phosphate composites combine the advantages of organic and inorganic materials, have good biocompatibility and osteoinductivity, and can promote the regeneration of bone tissue. Its degradation rate is adjustable, and the needs of different bone defect repairs can be met by adjusting the ratio of poly-ε-caprolactone and β-tricalcium phosphate. In addition, the material has good mechanical properties and can provide appropriate structural support. The good processing properties of poly-ε-caprolactone also enable the composite material to be prepared into various shapes and structures in a variety of ways to meet clinical needs.

[0004] CN106334217A discloses a method of preparing a poly-ε-caprolactone / β-tricalcium phosphate composite material by dissolving poly-ε-caprolactone in chloroform and mixing it with β-tricalcium phosphate, and then preparing a bone repair scaffold by 3D printing, which has a good bone repair effect. However, the degradation rate of organic / inorganic composite materials cannot match the bone regeneration rate, which may cause the composite material to remain in the body for too long or too short a time, affecting bone regeneration. Although the mechanical properties of organic / inorganic composite materials are enhanced compared to pure organic materials, there is still a gap compared to natural bone. In addition, the biological activity of organic / inorganic composite materials is limited, and the growth of bone tissue inside the scaffold may be limited, especially when the pore design is unreasonable, affecting the repair effect.

[0005] Therefore, it is desirable in the art to develop a bone repair scaffold that has a degradation rate that matches the bone regeneration rate and has good mechanical properties and biological activity. Summary of the invention

[0006] In view of the deficiencies of the prior art, the object of the present invention is to provide a composite porous bone repair scaffold and a preparation method and application thereof.

[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a composite porous bone repair scaffold, wherein the raw materials for preparing the composite porous bone repair scaffold include bone repair organic materials, bone repair inorganic materials, and poly (octanediol citrate / ethylene glycol) ester particles.

[0009] The present invention adds biodegradable poly (octanediol citrate / ethylene glycol) ester particles to bone repair organic materials and bone repair inorganic materials, thereby regulating the degradation rate of the bone repair scaffold, achieving matching of the degradation rate of the composite material with the new bone regeneration rate, and making the bone repair scaffold have good biocompatibility and high osteogenic activity, and can improve the mechanical properties of the bone repair scaffold, simulate the mechanical behavior of natural bone and improve the stability of the scaffold.

[0010] The composite porous bone repair scaffold provided by the present invention is an additively manufactured organic / inorganic composite porous absorbable bone repair scaffold modified with poly (octanediol citrate / ethylene glycol) ester particles.

[0011] Preferably, the raw materials for preparing poly(octanediol-citrate / ethylene glycol) ester microparticles include citric acid, octanediol, and ethylene glycol, wherein the molar ratio of citric acid to glycol (i.e., the total of octanediol and ethylene glycol) is 1:(0.8-1.2), such as 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, etc., and the molar ratio of ethylene glycol to 1,8-octanediol is 1:(0.8-1.2). The ratio is (0.01-100):1, for example, 0.01:1, 0.03:1, 0.05:1, 0.08:1, 0.1:1, 0.3:1, 0.5:1, 0.8:1, 1:1, 3:1, 5:1, 8:1, 10:1, 20:1, 30:1, 40:1, 50:1, 60:1, 70:1, 80:1, 90:1, 100:1, etc.

[0012] Preferably, the size of the poly(octanediol citrate / ethylene glycol) ester particles is 0.1-100 μm, for example, 0.1 μm, 0.3 μm, 0.5 μm, 0.8 μm, 1 μm, 3 μm, 5 μm, 8 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, etc.

[0013] Preferably, the bone repair organic material is a biodegradable polymer material, including any one or a combination of at least two of polylactic acid (PLA), polyhydroxyalkanoate (PHA), polyglycolic acid (PGA), polycaprolactone (PCL), polylactic acid-glycolic acid copolymer (PLGA), and polylactic acid (PDLA).

[0014] Preferably, the bone repair inorganic material comprises hydroxyapatite (HAp), β-tricalcium phosphate (β-TCP), bioactive glass (BG), calcium sulfate (CaSO 4 ) or a combination of at least two of them.

[0015] Preferably, the raw materials for preparing the composite porous bone repair scaffold include the following components in terms of weight percentage:

[0016] Bone repair organic materials 20-70%;

[0017] Bone repair inorganic materials 20-70%;

[0018] Poly(1,8-octanediol / ethylene glycol citrate) ester microparticles 0.01-10%.

[0019] Preferably, the raw materials for preparing the composite porous bone repair scaffold can be 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70% or the like in terms of weight percentage.

[0020] Preferably, the raw materials for preparing the composite porous bone repair scaffold can be calculated by weight percentage, and the amount of bone repair inorganic material can be 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, etc.

[0021] Preferably, the raw materials for preparing the composite porous bone repair scaffold can be calculated by weight percentage, and the amount of poly (octanediol citrate / ethylene glycol) ester particles can be 0.01%, 0.03%, 0.05%, 0.08%, 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, etc.

[0022] Preferably, the shape of the composite porous bone repair scaffold includes any one of a cube, a cylinder and a wedge.

[0023] Preferably, the pore structure of the composite porous bone repair scaffold includes any one of a triangle, a quadrilateral and a hexagon.

[0024] Preferably, the wire diameter of the composite porous bone repair scaffold is 0.05-0.4 mm, for example, 0.05 mm, 0.06 mm, 0.08 mm, 0.1 mm, 0.15 mm, 0.2 mm, 0.25 mm, 0.3 mm, 0.35 mm, 0.4 mm, etc.

[0025] Preferably, the pore size of the composite porous bone repair scaffold is 100-800 μm, for example, 100 μm, 150 μm, 200 μm, 250 μm, 300 μm, 350 μm, 400 μm, 450 μm, 500 μm, 550 μm, 600 μm, 650 μm, 700 μm, 750 μm, 800 μm, etc.

[0026] Preferably, the porosity of the composite porous bone repair scaffold is 50-90%, for example, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, etc.

[0027] Preferably, the pore connectivity of the composite porous bone repair scaffold is 95-100%, for example, 95%, 96%, 97%, 98%, 99%, 100%, etc.

[0028] In a second aspect, the present invention provides a method for preparing the composite porous bone repair scaffold as described in the first aspect, the preparation method comprising the following steps:

[0029] (1) mixing a bone repair organic material, a bone repair inorganic material, and poly(octanediol citrate / ethylene glycol) ester particles, melt blending, and extruding a wire to obtain a composite wire;

[0030] (2) Using additive manufacturing to prepare the composite wire obtained in step (1) into the composite porous bone repair scaffold.

[0031] Additive manufacturing technology has significant advantages in the manufacture of bone repair scaffolds. First, additive manufacturing technology can achieve personalized customization and provide tailor-made scaffolds according to the patient's specific bone defects, greatly improving the repair effect and surgical success rate. Secondly, additive manufacturing supports complex three-dimensional structural design, which can simulate the microstructure of natural bone and optimize the pore network, thereby promoting bone regeneration and blood supply. In addition, this technology can effectively reduce material waste during the production process because it only uses materials where they are needed, reducing production costs.

[0032] Preferably, the melt blending and wire extrusion in step (1) are carried out in a polymer molding processing equipment.

[0033] Preferably, the melt blending equipment includes any one of a twin-roll mill, an internal mixer, and a twin-screw extruder.

[0034] Preferably, the wire extrusion in step (1) is carried out by a single screw extruder.

[0035] Preferably, the additive manufacturing method in step (2) includes a molten deposition method. The additive manufacturing and optimization of the composite porous bone repair scaffold is performed by controlling the process parameters such as the nozzle temperature, printing speed, and layer height in the molten deposition method; at the same time, the printing temperature is controlled, and a heating device and a vacuum device are added to the 3D printer platform so that the printed bone repair scaffold is thermally cured on the 3D printer platform. The additively manufactured bone repair scaffold can be customized to any shape, preferably a cube, a cylinder, and a wedge. The pore structure of the additively manufactured bone repair scaffold can be in the shape of a triangle, a quadrilateral, a hexagon, etc.; the wire diameter of the composite porous bone repair scaffold is 0.05-0.4mm; the pore size is 100-800μm; the porosity is 50-90%; and the pore connectivity is 95-100%.

[0036] Preferably, step (2) specifically comprises: using a fused deposition method to print the composite wire obtained in step (1) to obtain the composite porous bone repair scaffold.

[0037] Preferably, the printing temperature is 60-80°C, such as 60°C, 65°C, 70°C, 75°C, 80°C, etc.

[0038] In a third aspect, the present invention provides an application of the composite porous bone repair scaffold as described in the first aspect in repairing bone defects, for example, it can be used to repair bone defects caused by diseases such as trauma, bone tumors, osteonecrosis, and congenital bone defects.

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] The present invention adds biodegradable poly (octanediol citrate / ethylene glycol) ester particles to bone repair organic materials and bone repair inorganic materials, thereby regulating the degradation rate of the bone repair scaffold, achieving matching of the degradation rate of the composite material with the new bone regeneration rate, and making the bone repair scaffold have good biocompatibility and high osteogenic activity, and can improve the mechanical properties of the bone repair scaffold, simulate the mechanical behavior of natural bone and improve the stability of the scaffold. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is a physical picture of the composite porous bone repair scaffold provided in Example 1, Example 2, and Example 3 of the present invention.

[0042] Figure 2 This is a graph showing the stress-strain test results of the composite porous bone repair scaffold and natural bone provided in Example 1 and Comparative Example 1.

[0043] Figure 3 This is a graph showing the test results of in vitro degradation experiments of the composite porous bone repair scaffolds provided in Example 4, Comparative Example 1, and Comparative Example 2 of the present invention.

[0044] Figure 4 This is a graph showing the results of a cell live-death experiment on the composite porous bone repair scaffold provided in Example 1 of the present invention.

[0045] Figure 5 This is a graph showing the osteogenic activity test results of the porous bone repair scaffolds provided in Comparative Example 1, Comparative Example 2, Example 1, and Example 5 of the present invention. DETAILED DESCRIPTION

[0046] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0047] Unless otherwise specified, some of the raw material information used in the preparation examples, comparative preparation examples, embodiments and comparative examples of the present invention is as follows:

[0048]

[0049] Preparation Example 1

[0050] In this preparation example, a poly (octanediol citrate / ethylene glycol) ester microparticle is provided, and the preparation method comprises the following steps:

[0051] 19.2 g of anhydrous citric acid was weighed into a round-bottom flask, and after nitrogen was used to remove oxygen through three passes and three rows, the flask was placed in a 160° C. oil bath for melting; after the anhydrous citric acid was completely melted, 10.22 g of 1,8-octanediol and 1.86 g of ethylene glycol were added, and then vacuum reacted at 140° C. for 1 hour; then the prepared poly(citric acid-1,8-octanediol / ethylene glycol) ester was dissolved in dimethyl sulfoxide, and it was dialyzed and purified with ultrapure water, and after dialysis, it was freeze-dried to obtain poly(citric acid-1,8-octanediol / ethylene glycol) ester; then dichloromethane was used to dissolve poly(citric acid-1,8-octanediol / ethylene glycol) ester, and poly(citric acid-1,8-octanediol / ethylene glycol) ester microparticles were prepared by an emulsion method, and the stirring speed was 2000 rpm; finally, freeze-dried to obtain poly(citric acid-1,8-octanediol / ethylene glycol) ester microparticles with a particle size of 30-70 μm.

[0052] Preparation Example 2

[0053] In this preparation example, a poly (octanediol citrate / ethylene glycol) ester microparticle is provided, and the preparation method comprises the following steps:

[0054] Weigh 19.2g of anhydrous citric acid into a round-bottom flask, remove oxygen with nitrogen, and place in a 160℃ oil bath to melt. After the anhydrous citric acid is completely melted, add 10.22g 1,8-octanediol and 1.86g ethylene glycol, followed by a vacuum reaction at 140°C for 1h; then dimethyl sulfoxide was used to dissolve the prepared poly(citric acid-1,8-octanediol / ethylene glycol) ester, which was dialyzed and purified with ultrapure water, and then freeze-dried to obtain poly(citric acid-1,8-octanediol / ethylene glycol) ester; then dichloromethane was used to dissolve the poly(citric acid-1,8-octanediol / ethylene glycol) ester, and poly(citric acid-1,8-octanediol / ethylene glycol) ester microparticles were prepared by an emulsion method at a stirring speed of 10000rpm; finally, freeze-dried to obtain poly(citric acid-1,8-octanediol / ethylene glycol) ester microparticles with a particle size of 0.5-3μm.

[0055] Preparation Example 3

[0056] In this preparation example, a poly (octanediol citrate / ethylene glycol) ester microparticle is provided, and the preparation method comprises the following steps:

[0057] 19.2 g of anhydrous citric acid was weighed into a round-bottom flask, and after nitrogen was used to remove oxygen through a three-way three-way flow, the flask was placed in a 160° C. oil bath for melting; after the anhydrous citric acid was completely melted, 4.38 g of 1,8-octanediol and 4.34 g of ethylene glycol were added, and then vacuum reacted at 140° C. for 1 hour; then the prepared poly(citric acid-1,8-octanediol / ethylene glycol) ester was dissolved in dimethyl sulfoxide, and it was dialyzed and purified with ultrapure water, and after dialysis, it was freeze-dried to obtain poly(citric acid-1,8-octanediol / ethylene glycol) ester; then dichloromethane was used to dissolve the poly(citric acid-1,8-octanediol / ethylene glycol) ester, and poly(citric acid-1,8-octanediol / ethylene glycol) ester microparticles were prepared by an emulsion method, and the stirring speed was 2000 rpm; finally, freeze-dried to obtain poly(citric acid-1,8-octanediol / ethylene glycol) ester microparticles with a particle size of 30-70 μm.

[0058] Comparative Preparation Example 1

[0059] In this comparative preparation example, a polycitrate-1,8-octanediol ester is provided, and the preparation method comprises the following steps:

[0060] 19.2 g of anhydrous citric acid was weighed into a round-bottom flask, and after nitrogen was used to remove oxygen through a three-way three-way flow, the flask was placed in a 160° C. oil bath for melting; after the anhydrous citric acid was completely melted, 14.6 g of 1,8-octanediol was added, and then vacuum reacted at 140° C. for 1 hour; then, polycitric acid-1,8-octanediol ester was dissolved in dimethyl sulfoxide, and it was dialyzed and purified with ultrapure water, and after dialysis, it was freeze-dried to obtain polycitric acid-1,8-octanediol ester (particle size of 0.5-3 μm).

[0061] Example 1

[0062] In this embodiment, a composite porous bone repair scaffold is provided, and the preparation method comprises the following steps:

[0063] 30 g of poly-ε-caprolactone, 60 g of β-tricalcium phosphate and 10 g of poly(octanediol citrate / ethylene glycol) ester particles provided in Preparation Example 1 were weighed respectively, and after simple mechanical stirring and mixing, they were placed in a double-roll mill for melt blending to prepare a poly-ε-caprolactone / β-tricalcium phosphate / poly(octanediol citrate-1,8-ethylene glycol) ester composite material; then, the poly-ε-caprolactone / β-tricalcium phosphate / poly(octanediol citrate-1,8-ethylene glycol) ester composite wire was prepared by further extrusion through a single-screw extruder; then, a cylindrical porous absorbable bone repair scaffold was printed by a melt deposition method, and the pore structure was hexagonal, so as to obtain the composite porous bone repair scaffold, which had a wire diameter of 0.1 mm, a pore size of 150 μm, a porosity of 90%, and a pore connectivity of 95%.

[0064] Example 2

[0065] In this embodiment, a composite porous bone repair scaffold is provided, and the preparation method comprises the following steps:

[0066] 50 g of polylactic acid, 45 g of hydroxyapatite and 5 g of poly(octanediol citrate / ethylene glycol) ester particles provided in Preparation Example 1 were weighed respectively, and after simple mechanical stirring and mixing, they were placed in an internal mixer for melt blending at a temperature of 65°C to prepare a polylactic acid / hydroxyapatite / poly(octanediol citrate / ethylene glycol) ester composite material; then, polylactic acid / hydroxyapatite / poly(octanediol citrate / ethylene glycol) ester composite wire was prepared by further extrusion through a single screw extruder; then, a cubic porous absorbable bone repair scaffold was printed by a melt deposition method, and the pore structure was hexagonal, so as to obtain the composite porous bone repair scaffold, which had a wire diameter of 0.1 mm, a pore size of 200 μm, a porosity of 80%, and a pore connectivity of 97%.

[0067] Example 3

[0068] In this embodiment, a composite porous bone repair scaffold is provided, and the preparation method comprises the following steps:

[0069] 30 g of polylactic acid-glycolic acid copolymer, 69 g of bioactive glass and 1 g of poly(octanediol-1,8-citrate / ethylene glycol) ester particles provided in Preparation Example 1 were weighed respectively, and after simple mechanical stirring and mixing, they were placed in a twin-screw extruder for melt blending at a temperature of 65°C to prepare a polylactic acid-glycolic acid copolymer / bioactive glass / poly(octanediol-1,8-citrate / ethylene glycol) ester composite material; subsequently, polylactic acid-glycolic acid copolymer / bioactive glass / poly(octanediol-1,8-citrate / ethylene glycol) ester composite wire was prepared by further extrusion through a single screw extruder; subsequently, a cubic porous absorbable bone repair scaffold was printed by a melt deposition method, and the pore structure was a quadrilateral, so as to obtain the composite porous bone repair scaffold, whose wire diameter was 0.3 mm, pore size was 600 μm, porosity was 70%, and pore connectivity was 99%.

[0070] Example 4

[0071] In this embodiment, a composite porous bone repair scaffold is provided, and the preparation method comprises the following steps:

[0072] 30 g of poly-ε-caprolactone, 60 g of β-tricalcium phosphate and 10 g of poly(octanediol citrate / ethylene glycol) ester particles provided in Preparation Example 2 were weighed respectively, mixed by simple mechanical stirring, and then placed in a double-roll mill for melt blending to prepare a poly-ε-caprolactone / β-tricalcium phosphate / poly(octanediol citrate-1,8-ethylene glycol) ester composite material; then further extruded by a single-screw extruder to prepare a poly-ε-caprolactone / β-tricalcium phosphate / poly(octanediol citrate-1,8-ethylene glycol) ester composite wire; then a cubic porous absorbable bone repair scaffold was printed by a melt deposition method, and the pore structure was triangular, so as to obtain the composite porous bone repair scaffold, whose wire diameter was 0.05 mm, pore size was 100 μm, porosity was 90%, and pore connectivity was 95%.

[0073] Example 5

[0074] The only difference between this example and Example 4 is that the poly(octanediol citrate / ethylene glycol) ester microparticles provided in Preparation Example 2 are replaced with poly(octanediol citrate / ethylene glycol) ester microparticles provided in Preparation Example 3 of equal mass.

[0075] Comparative Example 1

[0076] In this comparative example, a composite porous bone repair scaffold is provided, and the preparation method comprises the following steps:

[0077] 40 g of poly-ε-caprolactone and 60 g of β-tricalcium phosphate were weighed respectively, mixed with simple mechanical stirring, and then placed in a double-roll mill for melt blending to prepare a poly-ε-caprolactone / β-tricalcium phosphate composite material; then further extruded by a single-screw extruder to prepare a poly-ε-caprolactone / β-tricalcium phosphate composite wire; then printed a cubic porous absorbable bone repair scaffold by a melt deposition method, and the pore structure was triangular, so as to obtain the composite porous bone repair scaffold, which had a wire diameter of 0.05 mm, a pore size of 100 μm, a porosity of 90%, and a pore connectivity of 95%.

[0078] Comparative Example 2

[0079] The only difference between this comparative example and Example 4 is that the poly(octanediol citrate / ethylene glycol) ester microparticles are replaced with the polyoctanediol citrate obtained in Comparative Preparation Example 1.

[0080] For patients with bone defects, if there are no interfering factors such as metal foreign bodies in the defect area that affect the CT scan image, anatomical data can be obtained through CT scanning. Combined with the infection situation and the severity of the bone defect, a 3D printed scaffold with personalized appearance and physical and chemical properties is designed and implanted for the repair of bone defects. Bone repair scaffold products are designed in different shapes to meet the repair needs of different types of bone defects. Bone repair scaffold products of different shapes are designed according to mechanical requirements, anatomical structure and biocompatibility, with the aim of providing the best bone repair effect and tissue integration. Currently, the commonly used bone repair products in clinical practice are block, cylindrical and granular. Figure 1 The actual pictures of the composite porous bone repair scaffolds provided by the embodiments 1, 2 and 3 of the present invention are shown. According to the specific parameters such as the mechanical environment of the repair area, the defect area and degree, a personalized scaffold with a specific pore structure, characteristic material composition and specific shape can be realized by 3D printing technology for the repair of bone defects.

[0081] The mechanical strength of the poly-ε-caprolactone / β-tricalcium phosphate composite material is relatively low, especially compared with natural bone, and it is prone to insufficient strength. This results in it being unable to provide sufficient support in application scenarios that bear large mechanical stresses. The embodiment of the present invention adds bionic viscoelastic poly (octanediol citrate / ethylene glycol) ester particles to the poly-ε-caprolactone / β-tricalcium phosphate composite material to improve the mechanical properties of the bone repair scaffold, which can simulate the mechanical behavior of natural bone and improve the stability of the scaffold. At the same time, the addition of particles allows for more precise regulation of the mechanical properties of the material by controlling its size, distribution and proportion. Such as Figure 2 As shown, the composite porous bone repair scaffold provided in Example 1 has mechanical properties consistent with natural bone, thereby ensuring mechanical matching with natural bone and stability in bone defect repair. Figure 2 The stress-strain test method is as follows: the compressive performance of the composite porous bone repair scaffold is tested at a speed of 0.2 mm / min.

[0082] The degradation rate of the poly-ε-caprolactone / β-tricalcium phosphate composite material is slow, and it usually takes 2-3 years to completely degrade, which does not match the bone healing time (6-9 months). The long-term presence of the poly-ε-caprolactone / β-tricalcium phosphate composite material may induce local inflammatory reactions and affect the normal growth and maturation of new bone tissue. In the embodiment of the present invention, biodegradable poly (octanediol citrate / ethylene glycol) ester particles are added to the poly-ε-caprolactone / β-tricalcium phosphate composite material to adjust its degradation rate, thereby matching the rate of composite material degradation with new bone regeneration. The porous bone repair scaffolds provided in Example 4, Comparative Example 1, and Comparative Example 2 were subjected to an in vitro degradation experiment, and the test method was as follows: The composite porous bone repair scaffold was placed in Tris-HCl for an in vitro degradation experiment, and the extraction ratio was 30 ml / g. Samples were taken out within the corresponding degradation time, and after cleaning and drying, the remaining product mass was weighed, and the degradation rate was calculated. The test results are as follows: Figure 3 As shown, it can be seen that the addition of a small amount of poly (octanediol citrate / ethylene glycol) ester particles can significantly increase the degradation rate of the composite porous bone repair scaffold, thereby matching the new bone regeneration rate.

[0083] The osteogenic bioactivity of the poly-ε-caprolactone / β-tricalcium phosphate composite material is limited, and it cannot effectively promote the ability of osteoblasts to attach, proliferate or differentiate, and it is difficult to induce the formation of new bones. In the embodiment of the present invention, highly bioactive poly (octanediol citrate / ethylene glycol) ester particles are added to the poly-ε-caprolactone / β-tricalcium phosphate composite material to improve the osteogenic activity of the composite bone repair scaffold.

[0084] The composite porous bone repair scaffold provided in Example 1 was subjected to a cell live-death experiment. The test method was as follows: 2×10 4 MC3T3-E1 cells were seeded in a well plate and co-cultured with the composite porous repair scaffold in a culture medium. Live and dead cell staining solution was added at 24h, 48h, and 72h of co-culture, and then observed under a fluorescence microscope. The test results are shown in Figure 2. Figure 4 As shown, it can be seen that the poly-ε-caprolactone / β-tricalcium phosphate / poly (octanediol citrate / ethylene glycol) ester microparticle porous absorbable bone repair scaffold has good biocompatibility and can promote the proliferation of osteogenesis.

[0085] The osteogenic activity test of the porous bone repair scaffolds provided in Example 1, Example 5, Comparative Example 1, and Comparative Example 2 was performed as follows: 2×10 4MC3T3-E1 cells were seeded in a well plate and co-cultured with the composite porous repair scaffold in osteogenic medium. After 14 days of co-culture, they were fixed with 4% paraformaldehyde solution. After rinsing with PBS, each well was treated with an appropriate volume of Alizarin Red staining solution. After incubation, the staining solution was removed and gently washed 1-2 times with PBS solution until the color of the solution became lighter; finally, the cell staining was observed under an inverted microscope. The test results are as follows Figure 5 As shown, it can be seen that the addition of highly active material poly (octanediol citrate / ethylene glycol) ester particles makes the composite bone repair scaffold have good osteogenic properties.

[0086] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the composite porous bone repair scaffold and its preparation method and application, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A composite porous bone repair scaffold, characterized in that: The raw materials for preparing the composite porous bone repair scaffold include bone repair organic materials, bone repair inorganic materials, and poly (citrate-1,8-octanediol / ethylene glycol) ester particles.

2. The composite porous bone repair scaffold according to claim 1, characterized in that: The raw materials for preparing the poly(citrate-1,8-octanediol / ethylene glycol) ester microparticles include citric acid, 1,8-octanediol, and ethylene glycol, wherein the molar ratio of citric acid to glycol is 1:(0.8-1.2), and the molar ratio of ethylene glycol to 1,8-octanediol is (0.01-100):1; Preferably, the size of the poly(1,8-octanediol citrate / ethylene glycol) ester particles is 0.1-100 μm.

3. The composite porous bone repair scaffold according to claim 1 or 2, characterized in that: The bone repair organic material is a biodegradable polymer material, including any one of polylactic acid, polyhydroxyalkanoate, polyglycolic acid, polycaprolactone, polylactic acid-glycolic acid copolymer, and polylactic acid, or a combination of at least two thereof.

4. The composite porous bone repair scaffold according to any one of claims 1 to 3, characterized in that: The bone repair inorganic material includes any one of hydroxyapatite, β-tricalcium phosphate, bioactive glass, and calcium sulfate, or a combination of at least two of them.

5. The composite porous bone repair scaffold according to any one of claims 1 to 4, characterized in that: The raw materials for preparing the composite porous bone repair scaffold include the following components by weight percentage: Bone repair organic materials 20-70%; Bone repair inorganic materials 20-70%; Poly(1,8-octanediol / ethylene glycol citrate) ester microparticles 0.01-10%.

6. The composite porous bone repair scaffold according to any one of claims 1 to 5, characterized in that: The shape of the composite porous bone repair scaffold includes any one of a cube, a cylinder, and a wedge; Preferably, the pore structure of the composite porous bone repair scaffold includes any one of a triangle, a quadrilateral, and a hexagon; Preferably, the wire diameter of the composite porous bone repair scaffold is 0.05-0.4 mm; Preferably, the pore size of the composite porous bone repair scaffold is 100-800 μm; Preferably, the porosity of the composite porous bone repair scaffold is 50-90%; Preferably, the pore interconnectivity of the composite porous bone repair scaffold is 95-100%.

7. A method for preparing a composite porous bone repair scaffold according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: (1) mixing a bone repair organic material, a bone repair inorganic material, and poly(octanediol citrate / ethylene glycol) ester particles, and performing melt blending and wire extrusion to obtain a composite wire; (2) Using additive manufacturing to prepare the composite wire obtained in step (1) into the composite porous bone repair scaffold.

8. The preparation method according to claim 7, characterized in that: The melt blending and wire extrusion in step (1) are carried out in a polymer molding processing equipment; Preferably, the melt blending equipment includes any one of a twin-roll mill, an internal mixer, and a twin-screw extruder; Preferably, the wire extrusion is performed by a single screw extruder.

9. The preparation method according to claim 7 or 8, characterized in that: The additive manufacturing method in step (2) includes a molten deposition method; Preferably, step (2) specifically comprises: printing the composite wire obtained in step (1) by a fused deposition method to obtain the composite porous bone repair scaffold; Preferably, the printing temperature is 60-80°C.

10. Use of the composite porous bone repair scaffold according to any one of claims 1 to 6 in repairing bone defects.

Citation Information

Patent Citations

  • 3D printing PCL / beta-TCP composite material and preparation method, application and printing method thereof

    CN106334217A

Cited By

  • A toughened PLGA / P34HB composite material for bone tissue repair and a preparation method thereof

    CN122624747A